Microbiota Analysis of Biofilms on Experimental Abutments Mimicking Dental Implants: An In Vivo Model. Issue 10 (1st October 2017) - Cortés‐Acha, Berta; Figueiredo, Rui; Seminago, Ramón; Roig, Francisco J.; Llorens, Carlos; Valmaseda‐Castellón, Eduard
Abstract : Background: The microbiota colonizing dental implants has been said to be similar to the microbiome surrounding teeth. In the absence of inflammation, a biofilm with pathologic bacteria can cover implant surfaces exposed to the oral cavity, for example, due to a remodeling process. The aim of the present study is to identify microbiota surrounding exposed dental implants in patients with and without a history of periodontitis through a deep‐sequencing approach. Methods: An experimental abutment with the same surface and structure as a commercially available dental implant was used. Bacterial DNA was isolated, and the 16S ribosomal RNA gene was amplified and sequenced. Multiplexed tag‐encoded sequencing of DNA from the samples was performed, and the reads were processed by metagenomic rapid annotation. Results: A wide variety of bacteria, 96 species, were identified. The most frequently found bacteria were Fusobacterium nucleatum and Prevotella denticola. Some species generally associated with periodontitis were found to a greater extent in patients without a history of periodontitis. Some bacteria that have never been described as part of the oral microbiome were identified in the present sample. Conclusions: Analysis of data suggests that the bacteria surrounding exposed dental implants form a diverse microbiome regardless of the periodontal profile of patients. Further research is needed to clarify the role of these microorganisms in the oral environment.